Re-interpretation of the evidence for the PVC cell plan supports a Gram-negative origin - Devos, Damien (Antonie van Leeuwenhoek, 2013)
The PVC superphylum consists of the core phyla Planctomycetes, Verrucomicrobia and Chlamydiae, together with additional ones. Historically, the cell plan of PVC bacteria has been interpreted as an ‘exception’ to the classical Gram-negative (Gneg) one (Fuerst Antonie van Leeuwenhoek 104:451-466, 2013). However recent genomic and electron-microscopy data have argued against this exceptional status and suggested the need for a reinterpretation of the data in a more classical framework. In this perspective, I evaluate the arguments that have recently been presented by Fuerst as supporting the PVC cell plan as an ‘exception’ and present an alternative interpretation that is based on proposed evolutionary events that may have shaped the PVC genomes and proteomes. This interpretation supports the alternative proposal that the PVC cell plan is derived from a Gneg one.